2015
DOI: 10.18632/oncotarget.4521
|View full text |Cite
|
Sign up to set email alerts
|

Targeting annexin A2 reduces tumorigenesis and therapeutic resistance of nasopharyngeal carcinoma

Abstract: The expression of annexin A2 (ANXA2) in nasopharyngeal carcinoma (NPC) cells induces the immunosuppressive response in dendritic cells; however, the oncogenic effect and clinical significance of ANXA2 have not been fully investigated in NPC cells. Immunohistochemical staining for ANXA2 was performed in 61 patients and the association with clinicopathological status was determined. Short hairpin (sh)RNA knockdown of ANXA2 was used to examine cellular effects of ANXA2, by investigating alterations in cell prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 52 publications
2
43
0
Order By: Relevance
“…These results indicate that Annexin 2 may be an independent prognostic factor for hepatocellular carcinoma (20). Previous studies have demonstrated that the expression of Annexin A2 is significantly associated with metastasis and poor survival in nasopharyngeal and endometrial carcinoma, bladder cancer and serous ovarian cancer (21)(22)(23)(24). Using a proteomic assay, the present study identified that Annexin A2 was highly expressed in laryngeal carcinoma tissues, consistent with the results of the aforementioned studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results indicate that Annexin 2 may be an independent prognostic factor for hepatocellular carcinoma (20). Previous studies have demonstrated that the expression of Annexin A2 is significantly associated with metastasis and poor survival in nasopharyngeal and endometrial carcinoma, bladder cancer and serous ovarian cancer (21)(22)(23)(24). Using a proteomic assay, the present study identified that Annexin A2 was highly expressed in laryngeal carcinoma tissues, consistent with the results of the aforementioned studies.…”
Section: Discussionsupporting
confidence: 91%
“…The predictive efficiency of Annexin A2 combined with other Annexins in laryngeal carcinoma requires further investigation. Mechanically, silencing of Annexin A2 expression suppresses cell proliferation, adhesion, migration, invasion and vascular formation in nasopharyngeal carcinoma cells by downregulating epithelial-mesenchymal transition-associated signaling proteins (22). Decreased expression of Annexin A2 causes defects in tumor growth in vivo and cell proliferation in vitro without causing cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration, purity, and amount of total RNA were quantified using the Nano-Drop ND-1000 ultraviolet spectrophotometer (NanoDrop Technologies; Thermo Fisher Scientific, Inc.). Reverse transcription was conducted as previously described (31). qPCR was performed using the Fast SYBR ® -Green Master Mix (Invitrogen; Thermo Fisher Scientific, Inc.) on the ABI Step One Real-Time PCR system (ABI Corporation, Lee's Summit, MO, USA), according to the manufacturer's protocol.…”
Section: Rna Extraction and Reverse Transcription-quantitative Polymementioning
confidence: 99%
“…Such a method is expected to suffer from accuracy issue since the effect of IC mounting is not considered. Reference [2] precisely addresses the issue of erroneous chip impedance. Through measurement, antenna is redesigned iteratively to account for error in chip impedance [2].…”
Section: Introductionmentioning
confidence: 99%
“…Reference [2] precisely addresses the issue of erroneous chip impedance. Through measurement, antenna is redesigned iteratively to account for error in chip impedance [2]. However to reduce design cycle for inexpensive consumer wireless products it is preferable to have reasonably accurate chip impedance to start with.…”
Section: Introductionmentioning
confidence: 99%